Advanced engineering mathematics - Zill, Dennis G.; Zill, Dennis G. (Burlington, MA : Jone and Bartlett Learning, 2018)
Modern and comprehensive, the new sixth edition of Zill's Advanced Engineering Mathematics is a full compendium of topics that are most often covered in engineering mathematics courses, and is extremely flexible to meet the unique needs of courses ranging from ordinary differential equations to vector calculus. A key strength of this best-selling text is Zill's emphasis on differential equation as mathematical models, discussing the constructs and pitfalls of each.
Part 1: Ordinary differential equations -- Part 2: Vectors, matrices, and vector calculus Part 3: Systems of differential equations -- Part 4: Partial differential equations -- Part 5: complex analysis
Includes index.
Keywords: ENGINEERING MATHEMATICS